Pengaruh Kesehatan Mental, IQ dan SQ terhadap Kinerja Karyawan : Study Literatur pada Perusahaan Perbankan - Mellanie, Putri; Rimbano, Dheo; Veravayoda Veravayoda; Puspa, Fika; Karencia, Icha; Nora, Yepita (Universitas 45 Surabaya, 2025)
This study raises the issue of the importance of mental health, intelligence quotient (IQ), spiritual quotient (SQ) on employee performance and its impact on individuals and employee performance productivity in banking companies. This study aims to determine the effect of mental health, intelligence quotient (IQ), spiritual quotient (SQ) on employee performance literature studies in banking companies. The method used in this study is the systematic literature review (SLR) method. Data obtained from journals published on google scholar, open knowledge maps, elicit, sciencedirect, the total of all journals reviewed amounted to 45 journals.smpe situ. The results of this study indicate that mental health, intelligence quotient (IQ), spiritual quotient (SQ) on employee performance literature studies in banking companies affect individual awareness, ability to cope with stress, productivity, positive contribution to the community, able to solve problems, and wise in making decisions. Thus, mental health, intelligence quotient (IQ), spiritual quotient (SQ) on employee performance and improving their performance are important aspects that are interrelated for organizational success in banking companies.